Massive Right Atrial Thrombosis: Are You Brave Enough to Start Anticoagulation? A Case Report - Bergonti, Marco; Ascione, Ciro; Agostoni, Piergiuseppe; Castelli, Roberto; Vignati, Carlo (Frontiers in Cardiovascular Medicine, 2021)
Chronic myelomonocytic leukemia (CMML) is a clonal hematopoietic stem cell disorder with overlapping myelodysplastic and myeloproliferative features. The disease is generally characterized by blood monocytosis, bone marrow dysplasia, cytopenia, and hepatosplenomegaly. While malignant blood diseases are frequently associated with a high risk of thromboembolism, CMML is often accompanied by immune-mediated hemorrhagic diathesis. Indeed, very few reports in literature report thrombotic complications of CMML patients. We will briefly present here the case of a patient with CMML who developed a massive right atrial thrombus. We aim to highlight the non-negligible thrombotic burden of the disease, and we will get through the differential diagnosis of right atrial masses and the management of right atrial thrombi, which are a rare and poorly known entity.